TEACHERS' PERCEPTIONS OF COMPETENCE RELATED TO RUBRICS AND THE PROBLEMS THEY CONFRONT - Güneş, Perihan (International Online Journal of Education and Teaching, 2020)
The purpose of this research is to determine the competencies and difficulties experienced by science teachers in developing, using, and scoring rubrics. For this purpose, the descriptive survey model was used in the research. This study was conducted with 71 science teachers working in 12 different provinces of Turkey. The availability sampling method was used to determine the sample of the study. A survey of 17 items developed by researchers was used to determine teachers' views on the rubric. Personal information and Likert-type questions in the survey were analyzed with descriptive statistics. As a result, it was found that the teachers felt partially adequate in preparing and applying rubric and scoring, and faced some difficulties in these processes. It was determined that most science teachers had difficulty in understanding explanations, deciding on the appropriate subject, deciding on the type of rubric to be used, and the criteria of performance to be measured when preparing the rubric. It was also revealed that the limited level of knowledge of most teachers about rubrics partly affected their practice with these tools. Finally, it was found that the teachers were always objective and tolerant when scoring with rubrics, never giving close scores without looking at performance, sometimes affecting the student's overall success in class and disciplinary behavior. Keywords: Performance evaluation, rubric, science teacher, teacher efficacy.